(untitled) (The International Journal for Scientific Research, 2023)
This paper deals with the problems faced while trying to translate the English perfectives (present perfect simple and past perfect simple) into Arabic and suggested solutions to overcome these problems. It handles the tense system in English and Arabic and it shows how difficult the present perfect is for the non-native speakers of English. The paper reveals that little attention has been paid to the past perfect and the relationship between the two tenses has not been taken seriously in most grammar books. It aims to tackle the problem of translating the English present/past perfect into Arabic by suggesting some linguistic devices which can be of semantic and formal equivalents to the English perfect giving it a clear distinction from other tenses with the purpose of achieving the accurate meaning of the original. The researcher hopes that the findings of this study will, to a certain extent, help the translators, lexicographers and those who pay great attention to the contrastive studies.